Persepsi Peternak tentang Ayam IPB D-1 sebagai Ayam Lokal Unggul (Kasus Sinar Harapan Farm Jampang Tengah Sukabumi) - L. Cyrilla; C. Sumantri (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2022)
IPB D-1 chickens were produced from research on the application of molecular genetics with the aim of increasing the productivity and quality of Indonesian local chickens. This study aims to determine the perception of farmers at Sinar Harapan Farm Jampang Tengah Sukabumi about IPB D-1 chickens, which is viewed from the characteristics of innovations in IPB D-1 chickens. The research was conducted at Sinar Harapan Farm (SHF) which was located in Jampang Tengah District, Sukabumi Regency. Data collection was carried out in August 2020. Data collection was carried out by interviewing all 18 member farmers of Sinar Harapan Farm. SHF farmers’ perceptions of IPB D-1 chickens were measured from five characteristics of innovations in IPB D-1 chickens which included: relative advantage, compatibility, complexity, trialability, and observability. The results showed that the perception score for the aspect of relative advantage was 4.34, compatibility was 4.38, compatibility was 4.25, trialability was 4.13, and observability was 4.15. The farmers of Sinar Harapan Farm Jampang Tengah Sukabumi showed a good perception about IPB-D1 chickens.